Artificial repeated-rib roughness in a solar air heater – A review. (December 2019) - Chhaparwal, G.K.; Srivastava, Ankur; Dayal, Ram
Abstract: This review presents the development in artificial repeated-rib roughness or simply rib-roughness on the absorber plate of a solar air heater. The rib-roughness are of mainly four types: transverse, inclined, arc-shape and V-shape ribs. A critical investigation is done on these ribs to outline the evolution in design and resulting performance enhancement. This review reports the similarities and anomalies in the results through in-depth discussions on more than forty variables that can affect the SAH performance. This study emphasizes on exploring physics involved in the heat transfer and fluid flow around these ribs. A detailed discussion on the recent trends in repeated-rib roughness in SAH has been presented while drawing attention to their historical background.